Memories of La Plata, Argentina’s Flood (2013) in the Exhibition “Inundación y después” - Trípodi, María Victoria (2026)
Introduction: On April 2, 2013, the city of La Plata (Buenos Aires, Argentina) suffered the worst flood in its history, which left dozens dead. Objective: This paper analyzes how artistic practices contribute to the process of remembrance surrounding the event. Methods: A survey of the exhibitions displayed in the city in the years following the event was conducted, followed by an analysis of “Inundación y después” (2014), a project developed at the Museum of Art and Memory. Based on this, the curatorial narrative of the exhibition was examined, and the discourses conveyed by its various artistic works were studied. To this end, interviews were conducted with cultural actors linked to the project, and photographic records of the exhibition were analyzed. Results: The analysis made it possible to characterize the different artistic practices and identify different perspectives on the flood. Conclusions: The exhibition “Inundación y después” (2014) can be viewed as a vehicle and space for memory that, one year after the event, made it possible to revisit various aspects of the disaster. Furthermore, the exhibition offered participatory activities for the public that helped restore meaning to the event and fostered the formation of a collective memory.